Rethinking the Governance of the International Monetary Fund - Mirakhor, Abbas (IMF Working Papers; Working Paper ;, 2006)
This paper attempts to set out the principal issues that need to be resolved in formulating a proposal for quotas and voice reform in the IMF that could command broad support. Following John Rawls, we argue that "justice is the first virtue of social institutions," and we use his theory of justice to provide a method for understanding what should be the case, in the context of voice and voting shares, before international institutions, such as the IMF, are to be justifiable to their members. The implementation of this process suggests, among other things, that a major revision of the quota formulas is long overdue, and leaving this unaddressed raises serious questions regarding the IMF's governance which could develop into a core mission risk and jeopardize the relevance of the institution.